Heteroatom-Embedding Annulative π-Extension (Hetero-APEX) Reactions: An Overview - Ito, Hideto; Kawahara, Kou P.; Itami, Kenichiro (Synthesis, 2023)
Heteroatom-embedded polycyclic aromatic compounds (hetero-PACs) are a class of organic compounds contributing to a variety of research fields such as materials science, chemical biology, and so on. For applications using hetero-PACs, efficient preparation of hetero-PACs is essential. In particular, reactions transforming unfunctionalized aromatic compounds into hetero-PACs using appropriate heteroatom-containing aromatic compounds (π-extending agents) represent the most ideal way to prepare hetero-PACs. In this review, such heteroatom-embedding annulative π-extension (hetero-APEX) reactions, including their reaction mechanisms and scope of substrates, are described.1 Introduction2 Oxa-APEX Reactions3 Aza-APEX Reactions4 Thia-APEX Reactions5 Conclusion and Outlook
Keywords: annulative π-extension; polycyclic aromatic compounds; annulation; heteroaromatics; π-extended compounds; heteroles